Identificación de preferencias adaptables para los productores de café peruanos y colombianos: análisis desde el enfoque de capacidades - Flores Tenorio, Pedro (2003)
In the capability approach, there is a consideration about initial distribution ofwealth for assessing well-being, that permits to include individual’s own previousexperience in his income trajectories. Therefore, analysis of social costs or benefitsof different policies can be measured different from utilitarian way. In this paper, is analyzed the application of Amartya Sen and Martha Nussbaum proposalsabout adaptive preferences and the capabilities approach. After six years of crisis in the international coffee market, real income of theproducers decreased drastically. Many proposals exist to made good policies forimprove the welfare of peruvian coffee producers in this context, like it is madein other producing countries. The contribution of this paper is the identificationof adaptive preferences for coffee producers from Peru and Colombia, andanalyzing the basis of information that will be need for make such a goodpolicies. Finally, in this paper, are analyzed some subjective indicators of evaluation ofthe well-being for coffee producers in Perú and Colombia, like decrease in thesowed area, and other indicators of social impact that try to measure changes inwell-being. This paper will conclude that there are evidences of the process ofthe adaptive preferences in the cases of coffee producers from Peru and Colombia.